Features of the state of the neuroendocrine-immune complex and electrolyte-nitrogenous exchange under different variations of uric acid metabolism in female rats - Bombushkar, Igor (Journal of Education, Health and Sport, 2020)
Background. This article concludes the experimental part of the project "Physiological activity of uric acid". Our group previously identified 4 variants-clusters of uricemia and uricosuria both in rats and in humans. It was shown that the clusters differ from each other in the constellation of immune, autonomic and endocrine parameters as well as plasma and urine electrolytes and nitrogenous parameters, which to one degree or another correlate with uricemia and uricosuria. Because the autonomic, endocrine and immune parameters interact with each other within the neuro-endocrine-immune complex, the purpose of this study is to find out exactly which parameters of the neuro-endocrine-immune complex reflect the specificity of quantitative and qualitative clusters of uric acid metabolism. Materials and Methods. Experiment was performed on 60 healthy female Wistar rats 220-300 g. The plasma and urine levels of the uric acid, urea, creatinine, calcium, phosphates, chloride, magnesium, sodium and potassium (also in erythrocytes) as well as glucose (in plasma only) were determined. The parameters of the autonomic, endocrine and immune systems were registered. Results. 30 parameters of the neuroendocrine-immune complex and metabolism were identified, which collectively reflect the specificity of quantitative and qualitative clusters of uric acid metabolism. In addition to, by definition, uricemia and uricosuria, they represent markers of vagal tone, sympatho-vagal balance, androgenic, mineralocorticoid and glucocorticoid functions of the adrenal cortex as well as parathyroid activity; exchange of electrolytes (excretion with urine of sodium, calcium and phosphates, plasma levels of sodium, magnesium, chloride, phosphates and potassium and the latter in erythrocytes) and nitrogenous metabolites (creatininuria and plasma urea); as well as immunity parameters (the percentage of lymphoblasts, plasma cells and macrophages in the thymocytogram, the mass of the spleen, the entropy of the splenocytogram and the percentage of macrophages and microphages in it, the percentage of Th-, B- and 0-lymphocytes in the blood immunocytogram as well as blood level of leukocytes in general). Conclusion. The quantitative and qualitative clusters of uric acid metabolism are accompanied by specific constellations of parameters of the neuro-endocrine-immune complex and the electrolytes and nitrogenous compounds.